2012
DOI: 10.1111/j.1439-0396.2012.01309.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of oxalate poisoning in domestic animals: tolerance and performance aspects

Abstract: Summary Published data on oxalate poisoning in domestic animals are reviewed, with a focus on tolerance and performance. Oxalic acid is one of a number of anti‐nutrients found in forage. It can bind with dietary calcium (Ca) or magnesium (Mg) to form insoluble Ca or Mg oxalate, which then may lead to low serum Ca or Mg levels as well as to renal failure because of precipitation of these salts in the kidneys. Dietary oxalate plays an important role in the formation of Ca oxalate, and a high dietary intake of Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 57 publications
1
52
2
Order By: Relevance
“…This conclusion is supported by Rahman et al (2013) who suggested that limiting oxalate ingestion to <2.0% soluble oxalate of feed (DM basis) would be appropriate for protecting the ruminants from oxalate poisoning. In the present DM, dry matter; OM, organic matter; CP, crude protein; NDF, neutral detergent fibre; Ca, calcium; Mg, magnesium; Na, sodium; K, potassium; ME, metabolisable energy.…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…This conclusion is supported by Rahman et al (2013) who suggested that limiting oxalate ingestion to <2.0% soluble oxalate of feed (DM basis) would be appropriate for protecting the ruminants from oxalate poisoning. In the present DM, dry matter; OM, organic matter; CP, crude protein; NDF, neutral detergent fibre; Ca, calcium; Mg, magnesium; Na, sodium; K, potassium; ME, metabolisable energy.…”
Section: Resultssupporting
confidence: 69%
“…For example, Allison et al (1977) reported that certain levels of oxalate can be degraded by rumen microorganisms. In addition, ruminants adapted to diets with high oxalate content can tolerate oxalate levels that are lethal to non-adapted animals (Rahman et al 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations